Characterization of a Low Pathogenic Avian Influenza Virus (H6N1) Isolated from Turkeys - Lapin, E.; Perk, S.; Shkoda, I.; Davidson, I.; Inbar, A.; Geva, Z.; Rosenbluth, E. (Influenza Research and Treatment, 2011)
An avian influenza virus (AIV), A/turkey/Israel/09 subtype H6N1, was isolated from turkey poults exhibiting typical pathology associated with AIV infection. The virus was characterized by RT-PCR using AIV subtype-specific primers and by the haemagglutination inhibition test using AIV subtype-specific antisera. The virus has an intravenous pathogenicity index of 0 and possessed a nucleotide sequence at the cleavage site of the hemagglutinin gene, PQIETR*GLF, associated with avian influenza viruses of low pathogenicity. Unlike the two previous H6N2 isolates originating from domestic ducks and mallard, the A/turkey/Israel/09 (H6N1) was isolated from turkeys. The gene sequences of the A/turkey/Israel/09 (H6N1) virus show divergence from the former Israeli H6 isolates.